Development of a Creative Manual Book for Science Youth Scientific Group - Ismail Fikri Natadiwijaya; Lissa Lissa; Lesy Luzyawati (Mangifera Edu, 2021)
One of the world of education components that specifically aims to develop students' creativity is the Youth Scientific group (KIR). Based on the case studies, information was obtained that KIR participants generally still have difficulty generating ideas. Some of the factors that caused KIR participants' difficulty in creating ideas were lack of knowledge and the absence of a guide to guide them in making ideas. The purpose of this study was to develop a technical guidebook for making ideas for KIR students. Products are developed through development research in a sequence of steps: Define, design, and develop. This study provides the results that the product being developed has the following characteristics: 1) consists of 2 parts, namely the formation of new cognitive schemes and the formation of product idea designs, 2) The section on the formation of the New Cognitive Schema is designed based on the cognitive load theory, 3)The product idea design section is designed based on the Creative Process Learning theory. The product developed has a score with a very decent category but needs to be given significant improvements in the aspect of indicators and the addition of entrepreneurship material and SWOT analysis.